2010
DOI: 10.1038/oby.2009.439
|View full text |Cite
|
Sign up to set email alerts
|

BOUNCE: A Community‐based Mother–daughter Healthy Lifestyle Intervention for Low‐income Latino Families

Abstract: The primary purpose of this study was to assess the efficacy of a family‐based exploratory community study titled BOUNCE (Behavior Opportunities Uniting Nutrition, Counseling, and Exercise) to increase physical fitness and activity in low‐income Latino mothers and daughters. The BOUNCE study consisted of a 12‐week exercise (e.g., Latin dance), nutrition education, and counseling intervention. The design included a two‐arm parallel group assignment to an experimental group (EG; included 26 mother–daughter dyads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 12 publications
0
79
0
1
Order By: Relevance
“…48 In our study, the lack of significant pre-posttest increases in social support may be due to participants having to select their own social support partner to share the website with and give a pedometer to, as opposed to being assigned an exercise partner as part of the study. A potential limitation of this approach is that it relied on the use of existing social support networks, making it challenging for participants without social networks to select an exercise partner.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…48 In our study, the lack of significant pre-posttest increases in social support may be due to participants having to select their own social support partner to share the website with and give a pedometer to, as opposed to being assigned an exercise partner as part of the study. A potential limitation of this approach is that it relied on the use of existing social support networks, making it challenging for participants without social networks to select an exercise partner.…”
Section: Discussionmentioning
confidence: 74%
“…Previous physical activity interventions with Latinas have shown success for increasing social support through exercise or walking partners, 4648 using multiple approaches such as having the participant select an exercise partner from their own social network, 47 being assigned to or paired-up with another study participant, 46 or enrolling in a study as friend or family pairs. 48 In our study, the lack of significant pre-posttest increases in social support may be due to participants having to select their own social support partner to share the website with and give a pedometer to, as opposed to being assigned an exercise partner as part of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The age of participants in the interventions ranged from 18 to 95 years, although 85% ( n = 17) targeted middle-aged adults. Half of the interventions ( n = 10) specifically targeted females [18, 28, 30, 3235, 38, 39, 42], which may reflect the increased prevalence of obesity among Hispanic women [6]. In addition, several of the interventions recruited specific populations including low income ( n = 6) [3, 18, 30, 32, 35, 43], sedentary ( n = 4) [18, 28, 32, 40], obese ( n = 3) [28, 32, 39], those with diabetes ( n = 3) [3, 27, 29], and individuals at risk for cardiovascular disease ( n = 1) [33].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the design of the studies reported, 65% ( n = 13) were randomized controlled trials [18, 25, 28, 30, 3236, 39, 41, 44, 45], in which participants were randomly assigned to the intervention or control group. Two of the interventions were quasiexperimental [40, 42], which did not randomize the participants, yet still had a control or comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral nutrition research increasingly supports the notion that sustainable changes in eating behaviors must not only take into account the levels of influence from individual to societal, but also intervene with consumers on all of these levels [34,35]. For example, nutrition counseling should be personalized, but it is likely helpful to provide the context of population-based dietary guidance for improved understanding.…”
Section: Introductionmentioning
confidence: 99%